1978
DOI: 10.1111/j.1471-4159.1978.tb06530.x
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Mediated Blood‐brain Barrier Transport of Choline and Certain Choline Analogs

Abstract: Abstract— Blood‐brain barrier (BBB) transport of choline and certain choline analogs was studied in adult and suckling rats, and additionally compared in the paleocortex and neocortex of adult rats. Saturable uptake was characterized by a single kinetic system in all cases examined, and in adult rat forebrains we determined a Km= 442 ± 60 μM and Vmax= 10.0 ± 0.6 nmol min‐1 g‐1. In 14–15‐day‐old suckling forebrains a similar Km (= 404 ± 88 μM) but higher Vmax (= 12.5 ± 1.5 nmol min‐1 g‐1) was determined. When c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
106
2
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(115 citation statements)
references
References 67 publications
5
106
2
2
Order By: Relevance
“…3) was markedly reduced by 200 M quinine, 5 mM NMN, 1 mM choline, and 200 M tetrapentylammonium as established previously for rOCT2 (22). 2 Choline uptake via hOCT2 exhibited a similar inhibition profile, with 1 mM TEA replacing choline as an inhibitor (Fig. 3).…”
Section: Characterization Of Choline Transport By Octs-oocytessupporting
confidence: 81%
See 1 more Smart Citation
“…3) was markedly reduced by 200 M quinine, 5 mM NMN, 1 mM choline, and 200 M tetrapentylammonium as established previously for rOCT2 (22). 2 Choline uptake via hOCT2 exhibited a similar inhibition profile, with 1 mM TEA replacing choline as an inhibitor (Fig. 3).…”
Section: Characterization Of Choline Transport By Octs-oocytessupporting
confidence: 81%
“…6A). This uptake was largely potential-sensitive as demonstrated by the reduction in the tissue/medium ratio from 14 to 5 when the 2 concentration of potassium in the transport buffer was raised to 102.5 mM (Fig. 6A).…”
Section: Characterization Of Choline Transport By Octs-oocytesmentioning
confidence: 96%
“…Despite these restrictions, it has been shown that the charged quaternary ammonium molecule, choline, is transported across the BBB via a saturable carrier-mediated mechanism (Cornford et al, 1978). The plasma choline concentration in healthy adults is approximately 10 μM (Cohen et al, 1995), which is less than the calculated K m for the BBB choline transporter (Sawada et al, 1999;Allen and Smith, 2001;Kang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Choline is an essential nutrient that plays an important role as a precursor for the synthesis of the neurotransmitter acetylcholine (Cornford et al, 1978). Abnormal choline transport and metabolism have been implicated in a number of neurodegenerative disorders such as Alzheimer's and Parkinson's disease.…”
Section: Discussionmentioning
confidence: 99%
“…TRANSPORT D'AUTRES PETITES MO-LÉCULES Un système de transport pour la choline a également été décrit (Diamond, 1971;Cornford et al, 1978), ainsi que 2 systèmes de transport pour les précurseurs des acides nucléiques, l'un transportant l'adénine et l'autre certains nucléosides puriques et pyrimidiques (Cornford & Oldendorf, 1975 (Wu & Phillis, 1982;Stefanovich, 1983;Kalaria & Harik, 1986). Un système de transport a également été décrit pour les hormones thyroïdiennes (Pardridge & Mietus, 1980) et plusieurs systèmes de transport pour les vitamines : pyridoxine, acide pantothéni-que, biotine (Spector, 1978;Spector et al, 1986Spector et al, , 1987, thiamine monophosphate (Patrini et al, 1988 (Pardridge et al, 1985) et par des études sur de jeunes lapins (Duffy et al, 1986) (Pardridge, 1986) : celui du facteur insuline-like (Frank et aL, 1986), celui de la transferrine , celui d'albumine cationisée (Kumagai et al, 1986), celui de la leucineencéphaline (Zlokovic et aL, 1987).…”
Section: Transport Des Ionsunclassified